Maintenance Intravenous Fluid Prescribing Practices Among Paediatric Residents - Freeman, Michael A (2012)
AIM: To investigate the sodium composition of maintenance intravenous fluids used by paediatric residents throughout the United States in common clinical scenarios of arginine vasopressin excess. METHODS: We distributed an online survey to paediatric residency programs asking what type of maintenance intravenous fluids (0.2%, 0.45%, 0.9% NaCl or Lactated Ringers) they would administer in four common clinical scenarios of arginine vasopressin excess (gastroenteritis, pneumonia, meningitis and post-operative) in both a 6-month-old (mo) and a 13-year-old (yo) child. RESULTS: We had 472 responses, representing 5% of the total paediatric residency population in the US. Hypotonic maintenance intravenous fluids were selected in 78% of children (88.2% of 6 mo and 68.5% of 13 yo). Isotonic maintenance intravenous fluids were selected approximately twice as often for patients with meningitis as for those without (21.4% vs 8.7% 6 mo and 42.8% vs 27.7% 13 yo; p <.0.001). CONCLUSIONS: The majority of US paediatric residents would prescribe hypotonic maintenance intravenous fluids in disease states associated with arginine vasopressin excess. However, a significant number of residents are using isotonic maintenance intravenous fluids. Isotonic fluids are more likely to be prescribed in older children and children with meningitis.